Effects on hardness and microstructure of AISI 1020 low-carbon steel processed by high-pressure torsion - Diana Maritza Marulanda Cardona; Jittraporn Wongsa-Ngam; Hernando Jimenez; Terence G. Langdon (My University, 2017)
Low-carbon steel AISI 1020 was subjected to high-pressure torsion (HPT) with 6.0 GPa pressure through 1/4–5 turns. The microstructures of the samples in each turn were studied by means of X-ray diffraction (XRD) analyzing the changes in micro-strain, crystallite size and lattice parameter. Vickers testing was utilized to study the microhardness behavior of the samples subjected to HPT processing. The morphology evolution of the samples and especially the changes in ferrite and pearlite structures were studied for different numbers of turns using scanning electron microscopy (SEM).
Keywords: Vickers hardness test; Carbon steel; Metal and Thin Film Mechanics